Metaphor in the Song Lyrics of Aurora’s Album: A Different Kind of Human Step 2 - Muhammad Haziq Alwie Danial; Wiwin Widyawati (Aqlamuna: Journal of Educational Studies, 2024)
Metaphors are essential for understanding complex ideas and enhancing creativity. Thoroughly studying metaphors reveals their deeper meanings, especially in poetic devices used in songs. Artist Aurora is known for her inspiring and introspective lyrics, particularly in her album "A Different Kind of Human Step 2," which focuses on self-discovery and nature. Applying Lakoff and Johnson's theory of conceptual metaphors to Aurora's lyrics uncovers the depths of her emotions and highlights the environmental crisis she addresses. This research aims to identify the types of metaphors in Aurora's album and their meanings using Lakoff and Johnson's framework. The findings will benefit English teachers and learners by improving vocabulary, writing, and metaphor analysis skills through real-world song lyrics. The researcher will also contribute valuable knowledge to the field. The method used is library research, systematically analyzing various sources. The study found 30 lyrics containing conceptual metaphors, revealing the significance of structural, orientational, and ontological metaphors in creating meaning. This research offers valuable contributions to English Language Teaching by improving students' writing, vocabulary, and metaphorical comprehension.